Rapporter - Høffding, Simon; Aktor Liljedahl, Anders; Rex Pedersen, Rasmus; Reuter, Anders (Danish Yearbook of Musicology, 2017)
Research projects Simon Høffding: ‘A Phenomenology of Expert Musicianship’ Anders Aktor Liljedahl: ‘Robots in Music Videos: A Study of the Non-Human as Political Statement in African-American Popular Music Videos’ Rasmus Rex Pedersen: ‘Ad Hoc Entrepreneurs: Middle-Layer Musicians and the Contemporary Media Landscape’ Anders Reuter: ‘Pop as Minimalism: Objectivity, Repetition, and Spatial Staging in Pop Music’s New Software’